Amorphous nanocrystalline magnetically soft alloy and preparation method thereof
By designing the composition of amorphous and nanocrystalline soft magnetic alloys and employing heat treatment processes, the problem of thickness limitation in nanocrystalline strips has been solved, realizing high-frequency, high-permeability amorphous and nanocrystalline soft magnetic materials that meet the needs of high-frequency and miniaturized magnetic devices.
Patent Information
- Application Number
- CN202411385652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-14
AI Technical Summary
Existing technologies make it difficult to mass-produce nanocrystalline ribbons with a thickness of less than 14μm, which limits the improvement of the permeability of high-frequency, high-permeability filter devices and fails to meet the market's demand for high-frequency and miniaturized products.
By designing the composition of amorphous and nanocrystalline soft magnetic alloys and adding specific proportions of Mn and C elements, combined with planar flow casting and transverse magnetothermal treatment processes, amorphous ribbons with a thickness of 14~20μm were prepared, and the microstructure was optimized to improve high-frequency permeability.
A significant improvement in effective permeability at a high frequency of 100kHz has been achieved, with permeability exceeding 40,000, meeting the requirements for high-frequency and miniaturized magnetic devices.
Smart Images

Figure CN119314772A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-frequency filtering electronic devices, and in particular to an amorphous nanocrystalline soft magnetic alloy and a preparation method thereof. Background Art
[0002] Amorphous alloys are alloy materials obtained by cooling metals in a molten state at an extremely fast cooling rate. Due to the very fast cooling rate, the atoms in the alloy have become solid before they can arrange themselves regularly to form crystals. After fully solidified, the alloy retains the atomic structure of the liquid state. Due to the structural characteristics of the long-range disordered arrangement of atoms, it has a smaller structural correlation size and its anisotropy is much lower than that of similar crystalline materials. Therefore, it has a very small coercive force and exhibits better performance. However, this state is a non-equilibrium state. When external conditions change, the alloy tends to form a stable crystal structure, grains are precipitated on the amorphous alloy matrix, and the atoms inside the alloy nucleate and grow on the amorphous matrix. Appropriate crystallization treatment can control the size and structure of the crystals precipitated inside the alloy, which has a certain improvement on the performance of the alloy, especially when the grain size is at the nanometer level. The presence of nanocrystals makes the alloy exhibit more excellent soft magnetic properties.
[0003] Amorphous nanocrystalline soft magnetic alloys have good comprehensive soft magnetic properties: high saturation flux density (1.1~1.7T), high effective magnetic permeability (10 5 The devices made of amorphous nanocrystalline soft magnetic alloys have the characteristics of good high-frequency performance, small size, low loss, etc., and are currently widely used in common-mode inductors, wireless charging, transformers, new energy vehicles, mutual inductors and other fields.
[0004] With the continuous development of electronic power devices towards high frequency and the rapid development of new energy vehicles, the market has higher and higher requirements for the effective magnetic permeability μe of high frequency (above 100KHz) of filter devices. The higher the magnetic permeability of the filter device, the better the filtering effect. The current mainstream method to improve the high-frequency magnetic permeability is to reduce the thickness of the nanocrystalline strip. Due to the limitations of production equipment and processes, the preparation of nanocrystalline strips with a thickness of less than 14μm is very difficult and cannot be mass-produced and applied. The demand for a new type of high-frequency and high-permeability nanocrystalline alloy in industrial applications is becoming increasingly urgent. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high-frequency and high-permeability amorphous nanocrystalline soft magnetic alloy, a magnetic core and a preparation method thereof. The present invention obtains amorphous nanocrystalline soft magnetic materials with high frequency and high permeability by designing the composition of amorphous nanocrystalline soft magnetic alloy, which can meet the market demand for miniaturization and high frequency of magnetic devices.
[0006] In a first aspect, the present invention provides an amorphous nanocrystalline soft magnetic alloy, wherein the molecular formula of the amorphous nanocrystalline soft magnetic alloy is Fe g Mn a Si b B c C d Cu e Nb f ; Among them, 0.5≤a≤2, 12≤b≤16, 7≤c≤11, 0.25≤d≤1, 0.5≤e≤1.5, 2≤f≤4, and the sum of a~g is 100.
[0007] The amorphous nanocrystalline alloy of the present invention is based on Fe and is composed of elements such as Mn, Si, B, C, Cu, and Nb in specific proportions. Its atomic formula is Fe 100-a-b-c-d-f Mn a Si b B c C d Cu e Nb f ; Among them, the atomic molar percentage of each element is: 0.5≤a≤2, 12≤b≤16, 7≤c≤11, 0.25≤d≤1, 0.5≤e≤1.5, 2≤f≤4, and the rest is Fe and unavoidable impurities. This specific alloy uses Fe g Mn a Si b B c C d Cu e Nb f , by modulating the ferromagnetic coupling effect by the antiferromagnetic element manganese (Mn), and by adding the high resistivity element carbon (C) to increase the resistivity of the material, the permeability frequency loss caused by eddy current at a high frequency of 100kHz is effectively reduced. The amorphous nanocrystalline soft magnetic material with high frequency and high permeability provided by the present invention can meet the market demand for miniaturization and high frequency of magnetic devices.
[0008] Preferably, 0.5≤a≤1.2; and / or, 0.25≤d≤0.6. The present invention further optimizes the microstructure of the alloy by using Mn and C contents within the preferred range, so that the magnetic properties of the material at high frequencies are better modulated. The preferred Mn content further ensures the modulation effect of the antiferromagnetic elements, while the preferred carbon content further improves the resistivity of the material, thereby more effectively suppressing high-frequency eddy current losses and significantly improving the stability of magnetic permeability.
[0009] Preferably, b is 14 to 15; and / or c is 7.5 to 8.5.
[0010] The present invention provides a more precise element ratio, ensuring the best performance of the alloy in high-frequency applications. Through the precise control of the Mn content, the ferromagnetic coupling effect is more effectively modulated, and the resistivity of the material is better when the carbon content is within a specific range. At the same time, the precise adjustment of the Si and B contents further optimizes the microstructure of the alloy, so that the high-frequency magnetic permeability of the material is maximized while maintaining a low coercive force.
[0011] More preferably, a is 1±0.1; and / or d is 0.5±0.1; and / or b is 14.5±0.1; and / or c is 8±0.1.
[0012] Preferably, the amorphous nanocrystalline soft magnetic alloy is Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 . Through the reasonable combination of elements, the stability of the alloy is ensured, which can meet the application requirements of miniaturized and high-frequency magnetic devices. In particular, the alloy with this specific formula shows the most excellent high-frequency magnetic properties under the synergistic combination of the content of each element, and has good comprehensive performance. The alloy has low eddy current loss and excellent magnetic permeability at a high frequency of 100kHz.
[0013] Preferably, the strip thickness of the high-frequency and high-permeability amorphous nanocrystalline soft magnetic alloy is ≤20 μm; preferably 14-18 μm, and more preferably 14-16 μm.
[0014] In the second aspect, the method for preparing the high-frequency and high-permeability amorphous nanocrystalline soft magnetic alloy provided by the present invention includes preparing an amorphous thin strip by plane flow casting; preferably, it also includes rolling the amorphous thin strip into a circular magnetic core and performing heat treatment, and the heat treatment is preferably transverse magnetic heat treatment.
[0015] The present invention obtains a high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy by combining component design with a plane flow casting process and a transverse magnetic heat treatment process. The components of the present invention are prepared by a plane flow casting method using a beryllium copper alloy as a cooling crystallizer to prepare an amorphous strip of a certain thickness, the strip is sheared and wound into a ring sample, and the high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy is obtained by a specific heat treatment process to meet the 100KHz effective magnetic permeability μe>40000 of a 14~16μm nanocrystalline magnetic core, the effective magnetic permeability μe>36000 of a 100KHz nanocrystalline magnetic core, and the effective magnetic permeability μe>31000 of a 18~20μm nanocrystalline magnetic core.
[0016] Preferably, the heat treatment comprises firstly keeping warm at a first temperature and then keeping warm at a second temperature.
[0017] Preferably, the heat treatment comprises heating to a first temperature at a first rate and keeping the temperature; heating to a second temperature at a second rate and keeping the temperature; cooling to room temperature at a third rate; the second temperature is preferably 550-590°C.
[0018] More preferably, the first temperature is 400-420°C, and the second temperature is 560-580°C, preferably 560-570°C, and more preferably 570°C.
[0019] More preferably, the first rate is not higher than 5°C / min.
[0020] Preferably, the second rate and the third rate are not higher than 3°C / min.
[0021] Preferably, the first temperature is kept warm for 60 to 100 minutes.
[0022] Preferably, the second temperature is maintained for 60 to 150 minutes.
[0023] Preferably, magnetization is performed during the cooling process, and the magnetization time is 30 to 120 minutes, preferably 90 to 120 minutes.
[0024] By adopting the above-mentioned optimized heat treatment process, the present invention significantly improves the microstructure of the amorphous nanocrystalline soft magnetic alloy, and further enhances the magnetic properties of the material. First, heating to a first temperature at a certain rate and keeping the temperature can effectively remove the stress in the material and promote preliminary grain refinement; then, heating to a second temperature at a second rate and keeping the temperature for a certain period of time further optimizes the growth of nanocrystals of the alloy components of the present invention, so that the alloy has higher magnetic permeability and lower loss at high frequency. Then, the cooling process is controlled at a certain rate, and a magnetic field is applied at the same time, which can further enhance the magnetic domain structure of the material and significantly improve the directionality and stability of the magnetic permeability. The overall process further ensures the excellent performance of the alloy in high-frequency applications and better meets the market demand for high-frequency, high-permeability soft magnetic materials.
[0025] Preferably, the annular magnetic core has an outer diameter of 25±2 mm, an inner diameter of 20±2 mm, and a height of 30±2 mm.
[0026] Preferably, the method for preparing the high-frequency and high-permeability amorphous nanocrystalline soft magnetic alloy comprises.
[0027] 1) Raw material smelting: Add the raw materials according to the proportion into the medium frequency induction heating furnace for melting and smelting, melt them in an argon atmosphere, and then calm them for 30±5 minutes to ensure that the composition of the molten steel is uniform and without segregation.
[0028] 2) Preparation of amorphous strip: The calmed molten steel is cast at 1400~1500℃, and an amorphous thin strip with a width of 80~140mm and a thickness of 14~20μm is prepared by a copper mold single-roll quenching method.
[0029] 3) Magnetic core production: The prepared amorphous wide band is cut into narrow bands with a width of 30±2mm, and then wound into a circular magnetic core with an inner diameter of 20±2mm and an outer diameter of 25±2mm using an automatic winding machine. The specifications are defined as 25*20*30.
[0030] 4) Heat treatment: string the annular magnetic cores into a string of 20 to 30 and place them vertically in a vertical transverse magnetic heat treatment annealing furnace for the heat treatment and magnetization treatment.
[0031] In a third aspect, the magnetic core provided by the present invention comprises the amorphous nanocrystalline soft magnetic alloy or the amorphous nanocrystalline soft magnetic alloy prepared by the preparation method.
[0032] Preferably, the effective magnetic permeability of the magnetic core at 100KHz is greater than 26000; preferably 33192-42000, and more preferably 37746-41078.
[0033] The smaller the thickness of the nanocrystalline alloy strip, the higher the magnetic permeability at 100KHz after heat treatment. Finemet is an amorphous nanocrystalline soft magnetic alloy (typical composition 1K107: Fe 73.5 Si 13.5 B9Nb3Cu1;1K107B:Fe 73.5 Si 15.5 B7Nb3Cu1) The upper limit of the effective magnetic permeability μe of 100KHz material with a strip thickness of 14~16μm is about 38000, the upper limit of the effective magnetic permeability μe of 16~18μm material with a strip thickness of 100KHz is about 33000, and the upper limit of the effective magnetic permeability μe of 18~20μm material with a strip thickness of 100KHz is about 28000. The present invention provides a new high-frequency, high-magnetic permeability nanocrystalline soft magnetic alloy and a preparation method thereof, which has an effective magnetic permeability of 100KHz increased by more than 10% under the same strip thickness conditions as Finemet alloy. With the increase of frequency, the deterioration effect of high-frequency eddy current phenomenon on the magnetic permeability of the material becomes greater. Reducing high-frequency eddy current loss is an important method to improve the effective magnetic permeability of high frequency 100KHz. Reducing the strip thickness can significantly improve the high-frequency magnetic permeability of nanocrystalline strips, but due to the influence of production process, nanocrystalline strips below 14μm are very difficult to mass produce. Improving the resistivity of the alloy from the component side becomes another feasible direction. By adding Mn element to the Finemet alloy system to modulate the ferromagnetic exchange coupling between elements and adding C element to improve the resistivity of the alloy system, a new type of amorphous nanocrystalline soft magnetic alloy with high frequency and high magnetic permeability is obtained.
[0034] The amorphous nanocrystalline alloy component of the present invention is prepared into amorphous strips with thicknesses of 14-16 μm, 16-18 μm and 18-20 μm by a plane flow casting method using a beryllium copper alloy as a cooling crystallizer, and a specific heat treatment process is used to meet the requirements that the effective magnetic permeability μe of the 100KHz nanocrystalline magnetic core of 14-16 μm is greater than 40000, the effective magnetic permeability μe of the 100KHz nanocrystalline magnetic core of 16-18 μm is greater than 36000, and the effective magnetic permeability μe of the 100KHz nanocrystalline magnetic core of 18-20 μm is greater than 31000. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 XRD curves of the Fe-based amorphous nanocrystalline soft magnetic alloys provided in Examples 7-9 of the present invention.
[0037] Figure 2 DSC curves of the Fe-based amorphous nanocrystalline soft magnetic alloys provided in Examples 2, 4, and 7 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods. If no specific techniques or conditions are specified in the examples, they are all conventional methods or the techniques or conditions described in the literature in this field, or according to the product instructions. If the manufacturers of the reagents and instruments are not specified, they are all conventional products that can be purchased through regular channels.
[0040] The test method of the amorphous nanocrystalline soft magnetic alloy for the mutual inductor in the following embodiment is as follows: 1) X-ray diffraction analysis (XRD) method is used to verify whether the prepared alloy strip is a completely amorphous structure. To ensure that the alloy strip is a completely amorphous structure, the XRD spectra of all samples are from the free surface of the alloy strip (the other side relative to the copper roller surface); the relevant test conditions and parameters are: X-ray wavelength graphite monochromator filtering, tube voltage of 40kV, tube current of 30mA, test range of 20-90°, step length of 0.02°, scanning speed of 8° / min; in this application, the amorphous alloy strip can be determined by XRD spectrum. If its characteristic spectrum shows a broad diffraction peak (also known as "mantou peak"), it can be determined that the strip is a completely amorphous structure. The size of the nanocrystals after crystallization heat treatment is also obtained by X-ray diffraction analysis, and the size of the crystallized phase is calculated according to the Scherrer formula.
[0041] 2) Thermal analysis of the alloy strip was performed using differential scanning calorimetry (DSC) to examine the crystallization behavior and thermal stability of the alloy strip. Before the test, the strip was cut into small pieces with an area of less than 1mm×1mm, weighed about 20mg, and placed on the sample stand in an alumina crucible. The sample was heated under the protection of N2 atmosphere at a heating rate of 20℃ / min and a heating range of 300~800℃. By analyzing the DSC curve of the sample, the phase change of each sample during the heating process can be obtained, and the thermal characteristic temperature parameter values, such as Curie temperature, can be obtained. The characteristic temperature value of the DSC curve of the alloy strip can reflect the thermal stability of the alloy strip, provide a reference for determining the heat treatment process of the amorphous strip, and determine the approximate annealing temperature range. The first-level starting crystallization temperature of the alloy strip is marked as Tx1, and the second-level starting crystallization temperature is marked as Tx2 (that is, the temperature point where the Fe-(B, P) compound begins to precipitate), and the difference between the two starting crystallization temperatures is marked as ΔTx (definition: ΔTx=Tx2-Tx1).
[0042] 3) Use the LCR tester to test the inductance of the sample, and then calculate the magnetic permeability formula μ e =(L*L e ) / (N 2 *Ae*μ0) to get the value of effective magnetic permeability μe, where L is inductance (unit: H), Le is effective magnetic path length, N is the number of turns of the test winding, Ae is the cross-sectional area, and μ0 is the vacuum magnetic permeability (μ0=4π*10 -7 H / m). Strip thickness is measured by micrometer.
[0043] Example 1
[0044] The molecular formula of the Fe-based amorphous nanocrystalline soft magnetic alloy provided in this embodiment is: Fe 72.75 Mn 0.5 Si 14.5B8Nb3Cu1C 0.25 .
[0045] The preparation method of the Fe-based amorphous nanocrystalline soft magnetic alloy is as follows.
[0046] (1) Industrial pure iron, ferrosilicon, ferroboron, ferroniobium, copper, carbon, manganese and other raw materials of industrial purity are treated according to the molecular formula of Fe 72.75 Mn 0.5 Si 14.5 B8Nb3Cu1C 0.25 The ingredients were weighed and placed in a medium frequency induction melting furnace for 180 minutes. The molten steel was then cooled for 30 minutes. The temperature of the molten steel was kept at 1450°C and poured. The quenched amorphous strip with a width of 90-140 mm was prepared by a single roller quenching method using a beryllium copper alloy as a cooling crystallizer. The copper roller speed was 30 m / s. The thickness of the strip at the beginning of the pouring was 32 μm. The ductile-brittle transition thickness of the strip was determined by whether there was a brittle fracture area when the strip was torn transversely. The thickness of the strip was measured with a micrometer. Fe 72.75 Mn 0.5 Si 14.5 B8Nb3Cu1C 0.25 The ductile-brittle transition thickness of the amorphous alloy strip is 25 μm. The strip with a thickness of 18-20 μm is taken as the experimental sample, and the experimental sample is cut into a narrow strip with a width of 30 mm. The strip is wound into a magnetic core with a width of 30 mm, an inner diameter of 20 mm, and an outer diameter of 25 mm using an automatic winding machine.
[0047] (2) Fe 72.75 Mn 0.5 Si 14.5 B8Nb3Cu1C 0.25 The alloy was subjected to crystallization heat treatment, and the heat treatment equipment was a vertical transverse magnetic heat treatment annealing furnace. The core was heated to 400°C at a heating rate of 4°C / min and kept at that temperature for 80 minutes; then heated to 560°C at a rate of 3°C / min and kept at that temperature for 120 minutes; then cooled to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization was started when the temperature reached 500°C, and the magnetization time was 60 minutes. The magnetization magnetic field size was 1000Gs.
[0048] (3) Fe after heat treatment 72.75 Mn 0.5 Si 14.5 B8Nb3Cu1C 0.25 The alloy core is stored in a protective shell to ensure the roundness of the core and reduce the test error. The inductance value of the sample is obtained by using an LCR tester at a frequency of 100KHz and a test voltage of 0.3V, and then the magnetic permeability calculation formula μ is used. e =(L*L e ) / (N 2*Ae*μ0) to get the effective magnetic permeability μ of the core at 100KHz e The value of μ is obtained by test and calculation. e (100KHz)=28229.
[0049] Example 2
[0050] The components and preparation method of this embodiment are the same as those of embodiment 1, and only the heat treatment process is different. The process is to heat the core to 400°C at a heating rate of 4°C / min and keep it at that temperature for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, and the magnetization time is 60 minutes. The magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=30184.
[0051] Example 3
[0052] The components and preparation method of this embodiment are the same as those of embodiment 1, and only the heat treatment process is different. The process is to heat the core to 400°C at a heating rate of 4°C / min, and keep it at that temperature for 80 minutes; then heat it to 580°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, and the magnetization time is 60 minutes. The magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=26337.
[0053] Comparative Example 1
[0054] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 14.5 B8Nb3Cu1, the preparation method is the same as that of Example 1, and the ductile-brittle transition thickness is 25μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 560℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=26917.
[0055] Comparative Example 2
[0056] The components and preparation methods in this comparative example are the same as those in comparative example 1, except for the heat treatment process. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it at that temperature for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C. The magnetization time is 60 minutes and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=28468.
[0057] Comparative Example 3
[0058] The components and preparation methods in this comparative example are the same as those in comparative example 1, except for the heat treatment process. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it at that temperature for 80 minutes; then heat it to 580°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C. The magnetization time is 60 minutes and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=25798.
[0059] Comparative Example 4
[0060] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 15.5 B7Nb3Cu1, the preparation method is the same as that of Example 1, and the ductile-brittle transition thickness is 24μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 560℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=25501.
[0061] Comparative Example 5
[0062] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 15.5 B7Nb3Cu1, the preparation method is the same as that of Example 1. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min, and keep it at that temperature for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e(100KHz)=27523.
[0063] Comparative Example 6
[0064] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 15.5 B7Nb3Cu1, the preparation method is the same as that of Example 1. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min, and keep it at that temperature for 80 minutes; then heat it to 580°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=26722.
[0065] Comparative Example 7
[0066] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 13.5 B9Nb3Cu1, the preparation method is the same as that of Example 1, and the ductile-brittle transition thickness is 25μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 560℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=24884.
[0067] Comparative Example 8
[0068] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 13.5 B9Nb3Cu1, the preparation method is the same as that of Example 1. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min, and keep it at that temperature for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=26791.
[0069] Comparative Example 9
[0070] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 13.5B9Nb3Cu1, the preparation method is the same as that of Example 1. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min, and keep it at that temperature for 80 minutes; then heat it to 580°C at a rate of 3°C / min and keep it at that temperature for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature reaches 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=25031.
[0071] The specific performance results of Examples 1-3 and Comparative Examples 1-9 are shown in Table 1.
[0072] Table 1
[0073] The above embodiments and comparative examples have the highest 100KHz magnetic permeability when heat treated at 570°C, and the performance of the components of Si 14.5% and B 8% is the best. Adding Mn and C can effectively improve the 100KHz effective magnetic permeability of the alloy components.
[0074] Example 4
[0075] The molecular formula of the composition in this embodiment is: Fe 72.25 Mn 0.5 Si 14.5 B8 3.5 C1C 0.25 .
[0076] The preparation method of the Fe-based amorphous nanocrystalline soft magnetic alloy is as follows.
[0077] (1) Industrial pure iron, ferrosilicon, ferroboron, ferroniobium, copper, carbon, manganese and other raw materials of industrial purity are treated according to the molecular formula of Fe 72.25 Mn 0.5 Si 14.5 B8 3.5 C1C 0.25 The ingredients were weighed and placed in a medium frequency induction melting furnace for 180 minutes. The molten steel was then cooled for 30 minutes. The temperature of the molten steel was kept at 1450°C and poured. The quenched amorphous strip with a width of 90-140 mm was prepared by a single roller quenching method using a beryllium copper alloy as a cooling crystallizer. The copper roller speed was 30 m / s. The thickness of the strip at the beginning of the pouring was 32 μm. The ductile-brittle transition thickness of the strip was determined by whether there was a brittle fracture area when the strip was torn transversely. The thickness of the strip was measured with a micrometer. Fe 72.25 Mn 0.5 Si 14.5 B8 3.5 C1C 0.25The ductile-brittle transition thickness of the amorphous alloy strip is 25 μm. The strip with a thickness of 18-20 μm is taken as the experimental sample, and the experimental sample is cut into a narrow strip with a width of 30 mm. The strip is wound into a magnetic core with a width of 30 mm, an inner diameter of 20 mm, and an outer diameter of 25 mm using an automatic winding machine.
[0078] (2) Fe 72.25 Mn 0.5 Si 14.5 B8 3.5 C1C 0.25 The alloy was subjected to crystallization heat treatment, and the heat treatment equipment was a vertical transverse magnetic heat treatment annealing furnace. The core was heated to 400°C at a heating rate of 4°C / min and kept at that temperature for 80 minutes; then heated to 570°C at a rate of 3°C / min and kept at that temperature for 120 minutes; then cooled to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization was started when the temperature reached 500°C, and the magnetization time was 60 minutes. The magnetization magnetic field size was 1000Gs.
[0079] (3) Fe after heat treatment 72.25 Mn 0.5 Si 14.5 B8 3.5 C1C 0.25 The alloy core is stored in a protective shell to ensure the roundness of the core and reduce the test error. The inductance value of the sample is obtained by using an LCR tester at a frequency of 100KHz and a test voltage of 0.3V, and then the magnetic permeability calculation formula μ is used. e =(L*L e ) / (N 2 *Ae*μ0) to get the effective magnetic permeability μ of the core at 100KHz e The value of μ is obtained by test and calculation. e (100KHz)=31427.
[0080] Example 5
[0081] The molecular formula of the composition in this embodiment is: Fe 72 Mn 0.5 Si 14.5 B8 3.5 C1C 0.5 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 24 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=32974.
[0082] Example 6
[0083] The molecular formula of the composition in this embodiment is: Fe 71.75 Mn1Si 14.5 B8 3.5 C1C 0.25 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 24 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by testing. e (100KHz)=33026.
[0084] Example 7
[0085] The molecular formula of the composition in this embodiment is: Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 23 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=33192.
[0086] Comparative Example 10
[0087] The molecular formula of the ingredients in this comparative example is: Fe 71 Mn 1.5 Si 14.5 B8 3.5 C1C 0.5 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 23 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=28874.
[0088] Comparative Example 11
[0089] The molecular formula of the ingredients in this comparative example is: Fe 70.5 Mn2Si 14.5 B8 3.5 C1C 0.5 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 23 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=26483.
[0090] Comparative Example 12
[0091] The molecular formula of the ingredients in this comparative example is: Fe 71.25 Mn1Si 14.5 B8 3.5 C1C 0.75 The preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 23 μm. The heat treatment process is to heat the core to 400°C at a heating rate of 4°C / min and keep it warm for 80 minutes; then heat it to 570°C at a rate of 3°C / min and keep it warm for 120 minutes; then cool it to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization is started when the temperature is 500°C, the magnetization time is 60 minutes, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=29604.
[0092] Comparative Example 13
[0093] The molecular formula of the ingredients in this comparative example is: Fe 71 Mn1Si 14.5 B8 3.5 Cu1C1, the preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 22μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 570℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=27748.
[0094] Comparative Example 14
[0095] The molecular formula of the ingredients in this comparative example is: Fe 70 Mn2Si 14.5 B8 3.5 Cu1C1, the preparation method is the same as that of Example 4, and the ductile-brittle transition thickness is 22μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 570℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=25531.
[0096] The specific performance results of Example 2, Examples 4-7 and Comparative Examples 10-14 are shown in Table 2.
[0097] Table 2
[0098] Example 7: Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The sample with the same thickness has the highest effective magnetic permeability at 100KHz, which can reach 33192. Continuing with Example 7, Mn and C are added to the composition, the amorphous ability is weakened and the effective magnetic permeability at 100KHz is also reduced.
[0099] Example 8
[0100] The molecular formula of the composition in this embodiment is: Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 .
[0101] The preparation method of the Fe-based amorphous nanocrystalline soft magnetic alloy is as follows.
[0102] (1) Industrial pure iron, ferrosilicon, ferroboron, ferroniobium, copper, carbon, manganese and other raw materials of industrial purity are treated according to the molecular formula of Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5Weigh the ingredients in proportion, put them into the medium frequency induction melting furnace in turn, melt and smelt for 180 minutes, then calm the molten steel for 30 minutes, keep the molten steel temperature at 1450℃, and start pouring. Use the single roller quenching method with beryllium copper alloy as the cooling crystallizer to prepare the quenched amorphous strip with a width of 90~140mm. The copper roller speed is 30m / s. The thickness of the strip at the beginning of pouring is 30μm. The ductile-brittle transition thickness of the strip is determined by whether there is a brittle fracture area when the strip is torn horizontally. The thickness of the strip is measured with a micrometer. Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The ductile-brittle transition thickness of the amorphous alloy strip is 23 μm. The strip with a thickness of 16-18 μm is taken as the experimental sample, and the experimental sample is cut into a narrow strip with a width of 30 mm. The strip is wound into a magnetic core with a width of 30 mm, an inner diameter of 20 mm, and an outer diameter of 25 mm using an automatic winding machine.
[0103] (2) Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The alloy was subjected to crystallization heat treatment, and the heat treatment equipment was a vertical transverse magnetic heat treatment annealing furnace. The core was heated to 400°C at a heating rate of 4°C / min and kept at that temperature for 80 minutes; then heated to 570°C at a rate of 3°C / min and kept at that temperature for 120 minutes; then cooled to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization was started when the temperature reached 500°C, and the magnetization time was 60 minutes. The magnetization magnetic field size was 1000Gs.
[0104] (3) Fe after heat treatment 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The alloy core is stored in a protective shell to ensure the roundness of the core and reduce the test error. The inductance value of the sample is obtained by using an LCR tester at a frequency of 100KHz and a test voltage of 0.3V, and then the magnetic permeability calculation formula μ is used. e =(L*L e ) / (N 2 *Ae*μ0) to get the effective magnetic permeability μ of the core at 100KHz e The value of μ is obtained by test and calculation. e (100KHz)=37746.
[0105] Example 9
[0106] The molecular formula of the composition in this embodiment is: Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5.
[0107] The preparation method of the Fe-based amorphous nanocrystalline soft magnetic alloy is as follows.
[0108] (1) Industrial pure iron, ferrosilicon, ferroboron, ferroniobium, copper, carbon, manganese and other raw materials of industrial purity are treated according to the molecular formula of Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The ingredients were weighed and placed in a medium frequency induction melting furnace for 180 minutes. The molten steel was then cooled for 30 minutes. The temperature of the molten steel was kept at 1450°C and poured. The quenched amorphous strip with a width of 90-140 mm was prepared by a single roller quenching method using a beryllium copper alloy as a cooling crystallizer. The copper roller speed was 30 m / s. The thickness of the strip at the beginning of the pouring was 27 μm. The ductile-brittle transition thickness of the strip was determined by whether there was a brittle fracture area when the strip was torn transversely. The thickness of the strip was measured with a micrometer. Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The ductile-brittle transition thickness of the amorphous alloy strip is 23 μm. The strip with a thickness of 14-16 μm is taken as the experimental sample, and the experimental sample is cut into a narrow strip with a width of 30 mm. The strip is wound into a magnetic core with a width of 30 mm, an inner diameter of 20 mm, and an outer diameter of 25 mm using an automatic winding machine.
[0109] (2) Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The alloy was subjected to crystallization heat treatment, and the heat treatment equipment was a vertical transverse magnetic heat treatment annealing furnace. The core was heated to 400°C at a heating rate of 4°C / min and kept at that temperature for 80 minutes; then heated to 570°C at a rate of 3°C / min and kept at that temperature for 120 minutes; then cooled to room temperature at a cooling rate of 3°C / min. During the cooling process, transverse magnetization was started when the temperature reached 500°C, and the magnetization time was 60 minutes. The magnetization magnetic field size was 1000Gs.
[0110] (3) Fe after heat treatment 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 The alloy core is stored in a protective shell to ensure the roundness of the core and reduce the test error. The inductance value of the sample is obtained by using an LCR tester at a frequency of 100KHz and a test voltage of 0.3V, and then the magnetic permeability calculation formula μ is used. e =(L*L e ) / (N 2 *Ae*μ0) to get the effective magnetic permeability μ of the core at 100KHze The value of μ is obtained by test and calculation. e (100KHz)=41078.
[0111] Comparative Example 15
[0112] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 14.5 B8Nb3Cu1, the preparation method is the same as that of Example 8, and the ductile-brittle transition thickness is 25μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 570℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=33243.
[0113] Comparative Example 16
[0114] The molecular formula of the ingredients in this comparative example is: Fe 73.5 Si 14.5 B8Nb3Cu1, the preparation method is the same as that of Example 9, and the ductile-brittle transition thickness is 25μm. The heat treatment process is to heat the core to 400℃ at a heating rate of 4℃ / min, and keep it warm for 80min; then heat it to 570℃ at a rate of 3℃ / min and keep it warm for 120min; then cool it to room temperature at a cooling rate of 3℃ / min. During the cooling process, transverse magnetization is started when the temperature is 500℃, the magnetization time is 60min, and the magnetization magnetic field size is 1000Gs. The μ is calculated by test. e (100KHz)=37508.
[0115] The specific performance results of Examples 7-9 and Comparative Examples 12 and 15-16 are shown in Table 3.
[0116] Table 3
[0117] As can be seen from Table 3, the thinner the amorphous nanocrystalline strip is, the higher the effective permeability at high frequency 100KHz is. Under the influence of eddy current effect, adjusting the alloy composition to increase the resistivity can improve the high-frequency permeability. The thinner the strip is, the smaller the influence of high-frequency eddy current is, so increasing the resistivity of the composition will improve the high-frequency permeability more significantly on thick strips.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An amorphous nanocrystalline soft magnetic alloy, characterized in that: The molecular formula of the amorphous nanocrystalline soft magnetic alloy is Fe g Mn a Si b B c C d Cu e Nb f ; Among them, 0.5≤a≤2, 12≤b≤16, 7≤c≤11, 0.25≤d≤1, 0.5≤e≤1.5, 2≤f≤4, and the sum of a~g is 100.
2. The high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: 0.5≤a≤1.2; and / or, 0.25≤d≤0.
6.
3. The high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to claim 1 or 2, characterized in that: b is 14-15; and / or c is 7.5-8.
5.
4. The high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 3, characterized in that: a is 1±0.1; and / or, d is 0.5±0.1; and / or, b is 14.5±0.1; and / or, c is 8±0.1; Preferably, the amorphous nanocrystalline soft magnetic alloy is Fe 71.5 Mn1Si 14.5 B8 3.5 C1C 0.5 .
5. The high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 4, characterized in that: The strip thickness of the high-frequency and high-permeability amorphous nanocrystalline soft magnetic alloy is ≤20 μm; preferably 14 to 18 μm, and more preferably 14 to 16 μm.
6. The method for preparing the high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 5, characterized in that: The method comprises preparing an amorphous thin strip by plane flow casting; preferably, the method further comprises rolling the amorphous thin strip into a toroidal magnetic core and performing heat treatment, wherein the heat treatment is preferably a transverse magnetic heat treatment.
7. The method for preparing a high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: The heat treatment includes firstly maintaining the temperature at a first temperature and then maintaining the temperature at a second temperature; Preferably, the heat treatment comprises heating to a first temperature at a first rate and keeping the temperature; heating to a second temperature at a second rate and keeping the temperature; cooling to room temperature at a third rate; the second temperature is preferably 550-590°C.
8. The method for preparing a high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to claim 7, characterized in that: The first temperature is 400-420°C, and the second temperature is 560-580°C, preferably 560-570°C, and more preferably 570°C.
9. The method for preparing a high-frequency, high-permeability amorphous nanocrystalline soft magnetic alloy according to claim 7 or 8, characterized in that: The first rate is no higher than 5°C / min; and / or, the second rate and the third rate are not higher than 3°C / min; and / or, keeping the mixture at the first temperature for 60 to 100 minutes; and / or, keeping warm at the second temperature for 60 to 150 minutes; And / or, magnetization is performed during the cooling process, and the magnetization time is 30 to 120 minutes, preferably 90 to 120 minutes.
10. A magnetic core, characterized in that: Including the amorphous nanocrystalline soft magnetic alloy described in any one of claims 1-5 or the amorphous nanocrystalline soft magnetic alloy prepared by the preparation method described in any one of claims 6-9; preferably, the effective magnetic permeability of the magnetic core at 100KHz is greater than 26000; preferably 33192~42000, and more preferably 37746~41078.